2013
DOI: 10.1007/s13181-013-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lipid Emulsion Alters the Hemodynamic Response to Epinephrine in a Rat Model

Abstract: Intravenous lipid emulsion (ILE) is an adjunctive antidote used in selected critically ill poisoned patients. These patients may also require administration of advanced cardiac life support (ACLS) drugs. Limited data is available to describe interactions of ILE with standard ACLS drugs, specifically epinephrine. Twenty rats with intra-arterial and intravenous access were sedated with isoflurane and split into ILE or normal saline (NS) pretreatment groups. All received epinephrine 15 μm/kg intravenously (IV). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…137,[144][145][146] The safety of prolonged infusions (beyond 1 hour) has not been established. 147 The most common adverse effect of ILE therapy is interference with diagnostic laboratory testing 148 ; rare cases of pancreatitis 148 and pulmonary changes similar to those observed with acute respiratory distress syndrome 149 have also been reported. There appear to be complex pharmacodynamic interactions between ILE and epinephrine given during resuscitation, and in some situations, treatment with ILE alters the effectiveness of epinephrine and vasopressin in animal resuscitation studies.…”
Section: Nomentioning
confidence: 99%
“…137,[144][145][146] The safety of prolonged infusions (beyond 1 hour) has not been established. 147 The most common adverse effect of ILE therapy is interference with diagnostic laboratory testing 148 ; rare cases of pancreatitis 148 and pulmonary changes similar to those observed with acute respiratory distress syndrome 149 have also been reported. There appear to be complex pharmacodynamic interactions between ILE and epinephrine given during resuscitation, and in some situations, treatment with ILE alters the effectiveness of epinephrine and vasopressin in animal resuscitation studies.…”
Section: Nomentioning
confidence: 99%
“…4,5 The primary mechanism of action of epinephrine is on the α-receptor response, 6-8 thereby leading to increased coronary vascular pressure. Lipid administration delays the peak effect of epinephrine 9 and prolongs its duration of action on mean arterial pressure (MAP) but does not alter the peak increase in MAP or the heart rate (HR). Our recent work 10 demonstrated that a combination of lipid emulsion with epinephrine was superior to the administration of lipid emulsion alone with regard to successful resuscitation.…”
mentioning
confidence: 99%
“…Myocardial contraction is primarily driven by beta-oxidation of free fatty acids, a process which accounts for 50-70 % of myocardial ATP production. ILE, which is composed primarily of long chain fatty acids, provides a potential source of energy for the myocardium (Carreiro et al, 2013). In addition, intralipid infusion increases b-ketoacids and nitric oxide which stimulate insulin secretion and subsequently reverse the hypoinsulinemia induced by verapamil blockade of pancreatic islet-cell L-type calcium channels and so facilitate increased carbohydrate entry into myocytes (Tebbutt et al, 2006).…”
Section: Discussionmentioning
confidence: 99%